Weight regain after behavioural weight management programmes and its impact on quality of life and cost effectiveness: Evidence synthesis and health economic analyses. Issue 2 (2nd November 2022) - Hartmann‐Boyce, Jamie; Cobiac, Linda J; Theodoulou, Annika; Oke, Jason L.; Butler, Ailsa R; Scarborough, Peter; Bastounis, Anastasios; Dunnigan, Anna; Byadya, Rimu; Hobbs, F. D. Richard; Sniehotta, Falko F.; Amies‐Cull, Ben; et al.
Abstract: Aims: We used data from a recent systematic review to investigate weight regain after behavioural weight management programmes (BWMPs, sometimes referred to as lifestyle modification programmes) and its impact on quality‐of‐life and cost‐effectiveness. Materials and Methods: Trial registries, databases and forward‐citation searching (latest search December 2019) were used to identify randomized trials of BWMPs in adults with overweight/obesity reporting outcomes at ≥12 months, and after programme end. Two independent reviewers screened records. One reviewer extracted data and a second checked them. The differences between intervention and control groups were synthesized using mixed‐effect, meta‐regression and time‐to‐event models. We examined associations between weight difference and difference in quality‐of‐life. Cost‐effectiveness was estimated from a health sector perspective. Results: In total, 155 trials (n > 150 000) contributed to analyses. The longest follow‐up was 23 years post‐programme. At programme end, intervention groups achieved –2.8 kg (95%CI –3.2 to –2.4) greater weight loss than controls. Weight regain after programme end was 0.12‐0.32 kg/year greater in intervention relative to control groups, with a between‐group difference evident for at least 5 years. Quality‐of‐life increased in intervention groups relative to control at programme end and thereafter returned to control as the difference in weight between groups diminished. BWMPs with this initial weight loss and subsequent regain would be cost‐effective if delivered for under £560 (£8.80‐£3900) per person. Conclusions: Modest rates of weight regain, with persistent benefits for several years, should encourage health care practitioners and policymakers to offer obesity treatments that cost less than our suggested thresholds as a cost‐effective intervention to improve long‐term weight management. Registration: The review is registered on PROSPERO, CRD42018105744.